PRZEJŚCIOWA RÓŻNICA W PODATKU DOCHODOWYM A WARTOŚĆ AKTYWÓW NETTO - Kamiński, Ryszard (Wydział Prawa i Administracji UAM, 2001)
The method of book value is, relatively, the easiest and the least time-consuming method of enterprise assets’ valuation. However, the reliability of valuation by means of this method is questionable. The source of this doubt can be attributed to the problem of equivocal qualification of some liabilities to equities or to outside capital. Deferred incomes and charges are a particular example of the said liabilities. One of the reasons of showing deferred charges on the assets side and provisions on the liabilities side is the existence of a transitory difference in the income tax. The author of the paper raises the question if this difference influences the value of net assets, and if so, whether it depends on the way it is included in the formula of determining this value? It has been proved that the influence of the allocation for the transitory difference in the income tax on the value of net assets depends on the method of their classification when determining this value. It has also been proved that, at the point of calculating the value of net assets, there exists a problem of classifying some liabilities as equities or as outside capital and that it is needed that each and every part of a balance included in this calculation be dealt with individually.
TRANSITORY DIFFERENCE IN INCOME TAX VS. THE VALUE OF NET ASSETS